MANAGEMENT OF A SYMPTOMATIC CAROTID ATHEROSCLEROTIC DISEASE - UPDATE BASED ON INTERNATIONAL GUIDELINES - Kornelia Kaźmierkiewicz,; Emilia Piotrowicz,; Klaudia Michalak,; Kacper Janowski, (International Journal of Innovative Technologies in Social Science, 2025)
A significant proportion of all ischemic strokes is directly caused by atherosclerosis in the internal carotid artery. The diagnosis and management of patients experiencing ischaemic episodes lie at the intersection of neurology and vascular surgery. The text is largely based on the latest European Society for Vascular Surgery (ESVS) 2023 and AHA/ASA Guidelines 2021 recommendations at the time of publication, summarizing the management of symptomatic carotid artery stenosis.